Stage-Structured Harvest Models (Journal of Nonlinear Modeling and Analysis, 2024)
We formulate a stage-structured population model where the population is divided to two classes, the juveniles and the adults. Then, we includeharvest in the model and assume that the harvesting is only on adults. Thecases where the harvesting rate is constant, proportional to the number ofadults, or of Holling-II type are studied. While the model dynamics are relatively simple when the harvesting rate is proportional, the model system witha constant or a Holling-II type harvesting rate can have multiple positive equilibria. We explore the existence of all possible equilibria and investigate theirstability. We also give numerical examples to confirm our findings.
Keywords: Stage structure; Population; Harvesting rate; Holling-II type; Stability.